2003
DOI: 10.1554/0014-3820(2003)057[0119:mspate]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Systematics, Phylogeography, and the Effects of Pleistocene Glaciation in the Painted Turtle (Chrysemys Picta) Complex

Abstract: The painted turtle, Chrysemys picta, is currently recognized as a continentally distributed polytypic species, ranging across North America from southern Canada to extreme northern Mexico. We analyzed variation in the rapidly evolving mitochondrial control region (CR) in 241 turtles from 117 localities across this range to examine whether the painted turtle represents a continentally distributed species based on molecular analysis. We found strong support for the novel hypothesis that C. p. dorsalis is the sis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
68
1
6

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(83 citation statements)
references
References 53 publications
8
68
1
6
Order By: Relevance
“…We also see a striking pattern of reduced levels of genetic variation in the west (Table 3). Although a selective sweep could be responsible, we see the same pattern of east-west divergence and lower western diversity in painted turtles (Chrysemys picta complex; Starkey et al 2003). The most parsimonious explanation for such similar patterns in both turtles and frogs is some common geologic event, such as repeated glacial oscillations, that resulted in bottlenecks in both taxa in the west.…”
Section: Evolutionary History Of the Northern Leopard Frogsupporting
confidence: 58%
See 2 more Smart Citations
“…We also see a striking pattern of reduced levels of genetic variation in the west (Table 3). Although a selective sweep could be responsible, we see the same pattern of east-west divergence and lower western diversity in painted turtles (Chrysemys picta complex; Starkey et al 2003). The most parsimonious explanation for such similar patterns in both turtles and frogs is some common geologic event, such as repeated glacial oscillations, that resulted in bottlenecks in both taxa in the west.…”
Section: Evolutionary History Of the Northern Leopard Frogsupporting
confidence: 58%
“…That R. pipiens would show a major break across the Mississippi River was not an a priori prediction of our study. However, this result is not surprising because many other species of small mammals, fishes, amphibians, and reptiles also show major phylogeographic breaks in the vicinity of the Mississippi River (Blair 1965;Lansman et al 1983;Burbrink et al 2000 and references therein;Starkey et al 2003) Our analyses also revealed three interesting and unexpected patterns. First, NCA results suggest that the eastern haplotypes were derived from a western haplotype via longdistance colonization (Table 2).…”
Section: Do These Phylogenetic and Phylogeographic Patterns Fit Our Esupporting
confidence: 53%
See 1 more Smart Citation
“…An approximately 700-bp fragment of the mitochondrial displacement loop (d-loop) region was amplified for 114 specimens representing the panhandle and samples from deep within the ranges of each of the subspecies. Amplification and bidirectional sequencing was conducted using primers DES1 and DES2 (Starkey et al, 2003). Polymerase chain reaction (PCR) profile consisted of an initial denaturation for 5 min at 94°C; 35 cycles of 45 s at 94°C, 45 s at 52°C, and 45 s at 72°C; followed by a 5-min extension at 72°C.…”
Section: Molecular Datamentioning
confidence: 99%
“…Many Northern Hemisphere species, including freshwater fishes and turtles, show clear signatures of genetic bottlenecks and range reductions into isolated glacial refugia, followed by dramatic demographic and range expansion since the end of the last ice age (Starkey et al 2003;Seifertova et al 2012). Cyclic Pleistocene aridity in Australia appears not to have produced molecular signatures of wide-scale contraction to major refugia and subsequent macrogeographical range expansion as seen for temperate Northern Hemisphere biotas (Hewitt 2000).…”
Section: Historical Demography: Local Persistence or Northwards Expanmentioning
confidence: 99%